Reaksi Pasar atas Pengumuman Stock Split Sebelum dan Selama Pandemi COVID-19 - Wahyuni, Dewa Ayu Try; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 33 No 3 (2023)DO - 10.24843/EJA.2023.v33.i03.p04, 2023)
The study aims to examine differences in abnormal returns and stock trading volumes before and after stock split announcements in the period before and during the COVID-19 pandemic. The number of samples in this study were 47 companies selected by purposive sampling techniques. Data collection uses nonpartisan observation methods by accessing www.idx.co.id and yahoofinance.com sites. The data was analyzed using the Wilcoxon Signed Rank Test. The results showed that there was no difference abnormal return before and after the stock split announcement in the period before the COVID-19 pandemic, there was no difference in abnormal return before and after the stock split announcement during the COVID-19 pandemic, there was a difference in stock trading volume before and after the stock split announcement in the period before the COVID-19 pandemic, there was a difference in stock trading volume before and after the stock split during the COVID-19 pandemic. Keywords: Stock Split; Abnormal Return; TVA; COVID-19 Pandemic